" اسلامی تصوف کے مصادر اور مستشرقین كى آراء کا ایک تجزیاتی مطالعہ Origins of Islamic Sufism and a Critical study of the Opinions of the Orientalists " - عبد الوهاب جان الازهري (الإيضاح, 2014)
The issue of the source and origin of Sufism in Islam is a complex one. A number of scholars, since the latter half of the nineteenth century have put forward conflicting claims. Earlier Orientalists thought that a Sufism developed from a single source while the latter scholars think a number of different sources should be considered as origin of Sufism. Both groups agree, however, in maintaining that Sufism is an addition to Islam and did not originally belong to Islam. Different opinions have been presented regarding the true source of Sufism, for example, Persian, Indian, Christian, Jewish and Neo-Platonic philosophies. The present paper intends to refute these charges of external influences on Islamic Sufism and attempts to show that the real origin of Islamic Sufism lies nowhere but in the teachings of the Holy Qur’an, Sunnah of the Prophet (peace be upon him) and lives of the blessed companions of the Prophet (peace be upon him)..